Carbon supported catalysts in low temperature steam reforming of ethanol: study of catalyst performance1. Issue 61 (4th July 2015) - Rautio, Anne-Riikka; Seelam, Prem Kumar; Mäki-Arvela, Päivi; Pitkänen, Olli; Huuhtanen, Mika; Keiski, Riitta L.; Kordas, Krisztian
<x xml:space="preserve">Abstract</x> The difference in performance and deactivation of carbon supported catalysts in low temperature SRE are studied and explained.